Distributional Effects of the Panama Canal Expansion - Bussolo, Maurizio; De Hoyos, Rafael E.; Medvedev, Denis (2012)
This paper uses a dynamic macro-micro framework to evaluate the potential distributional effects of the expansion of the Panama Canal. The results show that large macroeconomic effects are only likely during the operations phase (2014 and onward), and income gains are likely to be concentrated at the top of the income distribution. The additional foreign exchange inflows during the construction and operations phases result in the loss of competitiveness of non-Canal sectors (Dutch disease) and in higher domestic prices, which hurt the poorest consumers. In addition, the construction and operation activities increase demand for more educated non-farm formal workers. Although these changes encourage additional labor movement out of agriculture and from the informal to the formal sector, much of the impact is manifested in growing wage disparities and widening income inequality. Using the additional revenues of the Canal expansion in a targeted cash transfer program such as "Red de Oportunidades", the Government of Panama could offset the adverse distributional effects and eradicate extreme poverty.